2011
DOI: 10.1111/j.1600-0412.2011.01130.x
|View full text |Cite
|
Sign up to set email alerts
|

Is a planned cesarean necessary in twin pregnancies?

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…While some observational studies have reported an increased risk of morbidity for vaginally delivered second twins (4-7), more recent observational studies, meta-analyses and decision analyses support the safety of vaginal delivery (8)(9)(10). In addition, a recent large randomized trial, the Twin Birth Study, demonstrated that a trial of labor was associated with improved maternal and infant outcomes when compared with planned cesarean delivery (11).…”
Section: Introductionmentioning
confidence: 89%
“…While some observational studies have reported an increased risk of morbidity for vaginally delivered second twins (4-7), more recent observational studies, meta-analyses and decision analyses support the safety of vaginal delivery (8)(9)(10). In addition, a recent large randomized trial, the Twin Birth Study, demonstrated that a trial of labor was associated with improved maternal and infant outcomes when compared with planned cesarean delivery (11).…”
Section: Introductionmentioning
confidence: 89%
“…In contrast to the above studies, other studies suggest VD as the preferred method of delivery, as they observe no benefit from CS in terms of neonatal outcome. These studies examined parameters such as perinatal mortality and serious neonatal morbidity at >32 weeks [22], morbidity and mortality at >30 weeks [39], neonatal complications including death at >34 weeks [50], neonatal composite morbidity or mortality for the second twin at >35 weeks [44], 1-min and 5-min Apgar scores and arterial cord pH for both twins [18], and perinatal mortality in monochorionic twins without twin-to-twin transfusion syndrome at >32 weeks of gestation [21], However, some of the above studies concerned active management of the delivery with maneuvers that are not considered safe by others, such as internal rotation and total breech extraction of unengaged second twins [12]. Studies concerning outcome in cases of breech first twins also report that there are no differences in neonatal mortality or morbidity between VD and CS [7,46].…”
Section: Mean Weight (Sd) (G)mentioning
confidence: 99%
“…In terms of perinatal outcomes, several studies have shown that planned cesarean delivery did not improve adverse outcomes and no differences between vaginal birth and planned cesarean delivery were observed [7,10,15,22]. A recent study using decision analysis did not support a policy of mandatory cesarean delivery of twins at or after 34 weeks of gestation [30]. Clinical decisions regarding the mode of delivery, until now, have been made primarily based on fetal presentation.…”
Section: Introductionmentioning
confidence: 96%
“…However, the optimal mode of delivery in cases of non-vertex second twins remains controversial due to concerns over the compromised safety of the second twin [5,10]. Nevertheless, the vaginal route remains an option for delivery of twin pregnancies with a vertex presentation of the first twin irrespective of the presentation of the second twin, as several studies have shown no clear benefit from planned cesarean deliveries in terms of neonatal outcomes [14,22,28,30].…”
Section: Introductionmentioning
confidence: 97%